Human Capital Formation: The Effect of a Miscarriage on Mental Health, Labour Market, and Family Outcomes - Sara Rellstab; Pieter Bakx; Pilar García-Gómez (Tinbergen Institute, 2022)
We investigate the effect of a miscarriage on mental health care use, labour market and family outcomes of women and their partners using Dutch linked ad- ministrative data. Miscarriages are common and largely random conditional on age. We estimate event study models using women with a completed pregnancy as a control group. A first miscarriage increases women\~As use of mental health ther- apy compared to the control group. These effects disappear over time. Partners are equally likely to use any mental health care as the control group. There are differences in labour market outcomes and probability of living together.
Keywords: J13; J16; I1; 330; health investment; education; human capital; health capital; dynamic optimal control; longevity